METTL3 inhibition reduces N6‐methyladenosine levels and prevents allogeneic CD4+ T‐cell responses. Issue 9 (17th September 2022) - Li, Shuang; Zou, Dawei; Chen, Wenhao; Britz, Gavin W; Liu, Zhaoqian; Weng, Yi‐Lan
Abstract: Alloreactive CD4 + T cells play a central role in allograft rejection. However, the post‐transcriptional regulation of the effector program in alloreactive CD4 + T cells remains unclear. N 6 ‐methyladenosine (m 6 A) RNA modification is involved in various physiological and pathological processes. Herein, we investigated whether m 6 A methylation plays a role in the allogeneic T‐cell effector program. m 6 A levels of CD4 + T cells from spleens, draining lymph nodes and skin allografts were determined in a skin transplantation model. The effects of a METTL3 inhibitor (STM2457) on CD4 + T‐cell characteristics including proliferation, cell cycle, cell apoptosis and effector differentiation were determined after stimulation of polyclonal and alloantigen‐specific (TEa; CD4 + T cells specific for I‐Eα52‐68 ) CD4 + T cells with α‐CD3/α‐CD28 monoclonal antibodies and cognate CB6F1 alloantigen, respectively. We found that graft‐infiltrating CD4 + T cells expressed high m 6 A levels. Administration of STM2457 reduced m 6 A levels, inhibited T‐cell proliferation and suppressed effector differentiation of polyclonal CD4 + T cells. Alloreactive TEa cells challenged with 40 μm STM2457 exhibited deficits in T‐cell proliferation and T helper type 1 cell differentiation, a cell cycle arrest in the G0 phase and elevated cell apoptosis. Moreover, these impaired T‐cell responses were associated with the diminished expression levels of transcription factors Ki‐67, c‐Myc and T‐bet. Therefore, METTL3 inhibition reduces the expression of several key transcriptional factors for the T‐cell effector program and suppresses alloreactive CD4 + T‐cell effector function and differentiation. Targeting m 6 A‐related enzymes and molecular machinery in CD4 + T cells represents an attractive therapeutic approach to prevent allograft rejection. Abstract : In this study, we found that STM2457 treatment reduced the levels of m 6 A RNA methylation, inhibited cell proliferation, induced G0 phase cell cycle arrest, promoted cell apoptosis and impaired effector differentiation of alloreactive TEa cells in response to alloantigen stimulation. The attenuated allogeneic T‐cell responses were associated with diminished expression levels of key transcription factors (e.g. T‐bet, c‐Myc) that control the T‐cell effector program. Therefore, METTL3 inhibition reduces the levels of m 6 A RNA methylation and inhibits allogeneic CD4 + T‐cell responses.